Beyond Intention: Analisis Perilaku Pengurangan Food Waste Melalui Pendekatan Extended TPB - Gregoria Natalie Golton; Suyanto Suyanto (SENTRI: Jurnal Riset Ilmiah, 2026)
The issue of food waste has become a growing global concern due to its negative impacts on the environment, economy, and food security. The increasing level of food waste indicates that consumer behavior has not fully supported the principles of sustainability. This condition highlights the importance of examining the factors influencing food waste reduction behavior. This study aims to analyze the effects of attitude, subjective norms, perceived behavioral control, environmental concern, economic impact, price consciousness, food taste, and cognition of food waste on intention to reduce food waste and food waste reduction behavior through the Extended Theory of Planned Behavior (E-TPB) approach. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 525 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The analysis included outer model and inner model evaluations to assess validity, reliability, and the relationships among variables in the proposed research model. The results showed that attitude, subjective norms, perceived behavioral control, and environmental concern positively influenced intention to reduce food waste. Subjective norms also had positive effects on attitude and perceived behavioral control. Intention to reduce food waste positively influenced food waste reduction behavior. Additional variables in the E-TPB model, namely economic impact, price consciousness, food taste, and cognition of food waste, were also found to positively affect food waste reduction behavior. The findings indicate that the E-TPB model provides a more comprehensive explanation of food waste reduction behavior through the integration of psychological, social, and economic.